Competitiveness analysis of Brazilian ethanol exports from 2004 to 2018: a constant market share approach - Ramos, Lucas Silva (2023)
Foreign trade has become increasingly important in countries’ economies. In a realistic view, one can consider that there is a tendency to increase Brazil’s participation in international trade in agribusiness products. In parallel with other major world food producers, Brazil has good relative conditions for expanding its production base. The country leads the world in sugar production and exports and is second in ethanol production and exports after the United States. Global demand for biofuels has risen sharply since the 2000s due to rising oil prices and fossil fuels’ impact on the environment. In this context, in terms of competitiveness, the question that arises is “How competitive is Brazil regarding its biofuelproduction,” considering not only the ability of biofuel to be an important ally in the environmental issue, but also an alternative to the oil derivatives market. Based on this context, the objective of this article was to analyze the panorama of the Brazilian competitiveness of biofuel, highlighting the performance of exports, evaluating the effect of world trade, the destination effect of exports, and the competitiveness effect in the period from 2004 to 2018, using the constant marketshare method. The main results found demonstrate that the Brazilian biofuel is competitive due to the increase in worldexports. Despite the competitiveness presented, Brazil is losing its share in the fuel market in recent years.